Enhancing performance, and combustion efficiency, and reducing tailpipe emissions of an engine fuelled with hydrogen-enriched diesel and ethanol blends at varying CRs using RSM - Rajak, Upendra; Apparao, K. Ch; Verma, Tikendra Nath; Agbulut, Umit (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Renewable fuels for internal combustion [IC] engines are needed due to the rapid depletion of fossil fuels. Using alcohol as fuel in compression ignition [CI] engines, either directly or as diesel blends, necessitates adjusting engine settings to reduce emissions without hunting performance. To enhance the efficiency of IC engines and reduce emissions, it is essential to ensure their compatibility with alternative energy sources. The investigation utilized a single-cylinder CI engine capable of operating on both gasoline and diesel. The engine was equipped with an electronic control system for exhaust emissions and a common rail fuel injection system. Various types of fuel were utilized, including diesel fuel [D100], ethanol [E] (10% and 20%), and hydrogen [H] (5 lpm, 10 lpm, 15 lpm). The study utilized an engine operating consistently at 1500 rpm with varying compression ratios [CR15:1-19:1] when it was under full load. The research looked at what happened to engine performance and emissions when different amounts of diesel fuel additives, specifically E (10%) and hydrogen, were used. The study showed that when hydrogen fuel was used, brake-specific fuel consumption [BSFC] went down. At full load, however, it was seen that the in-cylinder pressure values went up as the compression ratio [CR] (CR15:1 to CR19:1) went up. When the release data with the hydrogen fuel sample was examined, it showed that oxides of nitrogen [NOx] emissions went up a lot, which caused haze levels to rise too. Even so, emissions get worse when the hydrogen content goes above 10%.
Keywords: Hydrogen fuel; Response surface methodology; Diesel engine; Pollutant formation; Dual fuelling; COMPRESSION IGNITION ENGINE; Chemistry; Electrochemistry; Energy & Fuels